Spectroscopy, Structure, Biomacromolecular Interactions, and Antiproliferation Activity of a Fe(II) Complex With DPA-Bpy as Pentadentate Ligand - Bai, Hehe; Shi, Jia; Guo, Qingyu; Wang, Wenming; Zhang, Zhigang; Li, Yafeng; Vennampalli, Manohar; Zhao, Xuan; Wang, Hongfei (Frontiers in Chemistry, 2022)
A Fe(II) complex with DPA-Bpy (DPA-Bpy = N,N-bis(2-pyridinylmethyl)-2,20-bipyridine-6 -methanamine) as ligand was synthesized and characterized to mimic Bleomycin. The binding constants (Kb) of the complex with calf thymus DNA and human serum albumin (HSA) were quantitatively evaluated using fluorescence spectroscopy, with Kb as 5.53×105 and 2.40×104 M-1, respectively; and the number of average binding site (n) is close to 1. The thermodynamic analyses suggested that the electrostatic interactions exist between the complex and DNA, and the hydrogen bonding and Van der Waals force exist for the complex and HSA. The Fe complex exhibits the cleavage ability toward pBR322 DNA; and the crystal structure of HSA Fe complex adduct at 2.4 Å resolution clearly shows that His288 serves as the axial ligand of the Fe center complexed with a pentadentate DPA-Bpy ligand. Furthermore, the cytotoxicity of the complex was evaluated against HeLa cells. Both the Fe complex and the HSA Fe complex adduct show obvious effect on cell proliferation with a IC50 of 1.18 μM and 0.82 μM, respectively; they induced cell apoptosis and arrested cell cycles at S phase. This study provides insight into the plausible mechanism underlying their metabolism and pharmacological activity.